The Influence Of The Family Hope Program In Improving The Economy Of The Poor Community Beneficiaries (Case Study Of Tanjung Selamat Village Medan Tuntungan District) - Damanik, Ricky Maharani; Hasanah, Uswatun (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The Family Hope Program (PKH) is a social assistance program provided to help poor families in rural areas. According to the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 1 of 2018 concerning the Family Hope Program, it is explained that